A history of twentieth-century American women's poetry - Kinnahan, Linda A. (Cambridge university press, 2016)
"A History of Twentieth-Century American Women's Poetry explores the genealogy of modern American verse by women from the early twentieth century to the millennium. Beginning with an extensive introduction that charts important theoretical contributions to the field, this History includes wide-ranging essays that illuminate the legacy of American women poets. Organized thematically, these essays survey the multilayered verse of such diverse poets as Edna St Vincent Millay, Marianne Moore, Anne Sexton, Adrienne Rich, and Audre Lorde. Written by a host of leading scholars, this History also devotes special attention to the lasting significance of feminist literary criticism. This book is of pivotal importance to the development of women's poetry in America and will serve as an invaluable reference for specialists and students alike"--